2017
DOI: 10.1371/journal.pone.0189402
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid receptor mRNA levels in heart and white adipose tissue are associated with obesity in mice and humans

Abstract: BackgroundLysophosphatidic acid (LPA) receptor signaling has been implicated in cardiovascular and obesity-related metabolic disease. However, the distribution and regulation of LPA receptors in the myocardium and adipose tissue remain unclear.ObjectivesThis study aimed to characterize the mRNA expression of LPA receptors (LPA1-6) in the murine and human myocardium and adipose tissue, and its regulation in response to obesity.MethodsLPA receptor mRNA levels were determined by qPCR in i) heart ventricles, isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
1
14
1
Order By: Relevance
“…In all depots examined, expression of Lpar6 predominated. This is different from a prior report in mouse perigonadal WAT, cultured 3 T3‐L1 adipocytes, and human subcutaneous adipose tissue, where Lpar6 was among the more abundant Lpar expressed, but was detected at comparable levels to other lysoPtdOH ‐receptors (Brown et al, ). The next most abundant Lpar in all WAT depots we examined was Lpar1 that was ~3–15 fold less abundant than Lpar6 .…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In all depots examined, expression of Lpar6 predominated. This is different from a prior report in mouse perigonadal WAT, cultured 3 T3‐L1 adipocytes, and human subcutaneous adipose tissue, where Lpar6 was among the more abundant Lpar expressed, but was detected at comparable levels to other lysoPtdOH ‐receptors (Brown et al, ). The next most abundant Lpar in all WAT depots we examined was Lpar1 that was ~3–15 fold less abundant than Lpar6 .…”
Section: Resultscontrasting
confidence: 99%
“…). Our findings are in agreement with a prior report on perigonadal WAT, showing that expression of Lpar1–6 were not significantly altered by fasting when mice are fed chow (Brown et al, ). However, in that report, fasting did significantly induce perigonadal Lpar3 and Lpar5 when mice were fed a high‐fat and high‐sucrose diet for 16 weeks prior to testing, suggesting that Lpar may become responsive to hormonal or energetic signals of nutritional status under some conditions.…”
Section: Resultssupporting
confidence: 94%
“…Our understanding of the relationship between the ATX-LPA pathway and obesity can be improved by examining circulating LPA levels in human cohorts, in addition to ATX expression and activity. Brown et al [ 16 ] demonstrated that mRNA levels of distinct LPA receptors in insulin sensitive mouse and human tissues are associated with obesity. For example, LPA4, LPA5, and/or LPA6 are significantly increased in myocardial tissue and cells from HFHS-fed mice and humans with preobesity or obesity [ 16 ].…”
Section: Atx-lpa Signaling In Obesitymentioning
confidence: 99%
“…Brown et al [ 16 ] demonstrated that mRNA levels of distinct LPA receptors in insulin sensitive mouse and human tissues are associated with obesity. For example, LPA4, LPA5, and/or LPA6 are significantly increased in myocardial tissue and cells from HFHS-fed mice and humans with preobesity or obesity [ 16 ]. These data suggest that changes in tissue LPA receptor expression may also contribute to alterations in ATX-LPA signaling during obesity.…”
Section: Atx-lpa Signaling In Obesitymentioning
confidence: 99%
See 1 more Smart Citation